Pengalaman Siswa Kelas Rendah Sekolah Dasar Kota Sorong dalam Kegiatan Pojok Baca, Reels Video dan AI - Alfiah Junyani Arsyad (TSAQOFAH, 2026)
Learning among lower-grade elementary school students requires strategies that can provide active, engaging, and meaningful learning experiences through the use of media appropriate to students’ characteristics. This study aims to describe the experiences of lower-grade elementary school students in Sorong City in learning activities that integrate a reading corner, Reels videos, and Artificial Intelligence (AI). This study used a qualitative approach with a descriptive research design. The study was conducted at SD Yapis An-Nur, Sorong City, involving four Grade I students as the main participants and one classroom teacher as a supporting informant. Data were collected through observation, semi-structured interviews, and documentation during four learning meetings. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was obtained through source and technique triangulation. The results showed that students gave positive responses to the learning activities. In the reading corner activities, students actively selected and read books, especially picture books and children’s stories. The use of Reels videos helped students focus their attention and answer simple questions related to the material, while the use of AI fostered curiosity and encouraged students to ask simple questions about technology. Although each student showed different interests in the learning media, all participants remained engaged in the learning activities. The conclusion of this study affirms that the integration of a reading corner, Reels videos, and AI can support active, engaging, and meaningful learning experiences for lower-grade students when used purposefully with teacher guidance. These findings imply the importance of adaptively utilizing literacy and technology media in elementary school learning.